Why didn't you just do what you were told? : essays - Diski, Jenny (Bloomsbury Publishing, 2020)
Jenny Diski was a fearless writer, for whom no subject was too difficult, even her own diagnosis with cancer. Her columns in the London Review of Books -- selected here by her editor and friend Mary-Kay Wilmers, ranged from subjects as various as happiness, social psychology, self-absorption and cats -- have been described as 'virtuoso performances', and 'small masterpieces'.